The efficacy of transarterial chemoembolization combined with helical iodine-125 seed implant, lenvatinib and PD-1 inhibitors in patients with hepatocellular carcinoma complicated by main portal vein tumor thrombus: a retrospective study - Lin, Jia-Wen; Zhang, Shen; Shen, Jian; Yin, Yu; Yang, Jun; Ni, Cai-Fang; Wang, Wan-Sheng (Frontiers in Oncology, 2025)
PurposeTo evaluate the efficacy and safety of a multimodal therapeutic approach involving transarterial chemoembolization (TACE) in conjunction with helical iodine-125 (I-125) seed implant, lenvatinib, and programmed cell death-1(PD-1) inhibitors for hepatocellular carcinoma (HCC) complicated by main portal vein tumor thrombus (MPVTT).Material and methodsHCC patients with MPVTT treated with TACE coupled with helical I-125 implant, lenvatinib, PD-1 inhibitors between September 2019 and August 2022 were retrospectively analyzed, and constituted as study group. Those treated with TACE, helical I-125 seed implant, and sorafenib between December 2016 and August 2020 served as the historical control group. All patients received sorafenib or lenvatinib combined with PD-1 inhibitors within 3–7 days after TACE and helical I-125 seed implantation. The longest follow-up period for all patients in both groups was 36 months from the date of helical I-125 seed implantation. Primary outcome was overall survival time (OS), and secondary outcomes were progression free survival time (PFS), objective response rate (ORR), and disease control rate (DCR). The Cox proportional hazards regression model was employed to identify independent prognostic factors influencing OS and PFS. The value P < 0.05 was deemed statistically significant.ResultsA total of 53 patients were enrolled, with 22 assigned to the study group and 31 to the control group. The study group exhibited superior overall ORR(54.5% vs. 25.8%, P = 0.033) and overall DCR (77.3% vs. 64.5%, P = 0.319). Notably, the ORR and DCR of MPVTT were higher in the study group (86.4% vs. 51.6%, P = 0.008; and 95.5% vs. 83.9%, P = 0.382, respectively). Median OS (16.1 ± 6.1 months vs. 10.2 ± 0.8 months, P = 0.008) and PFS (13.6 ± 3.0 months vs. 6.1 ± 0.6 months, P = 0.014) were prolonged in the study group. The maximal tumor size, alpha fetoprotein level, and treatment modality were independent predictors for OS, while the maximal tumor size and treatment modality were independent determinants for PFS. Study group showed frequent hypothyroidism and reactive cutaneouscapillary (P < 0.01), with comparable grade 3/4 adverse events between groups.ConclusionsThe integration of the helical I-125 seed implant with TACE, lenvatinib, and PD-1 inhibitors is the safe and efficacious approach in the management of HCC complicated by MPVTT.